Adventure on the amazon - Osborne, Mary Pope; Masson, Philippe (London Fox red, 2022)
Eight-year-old Jack, his seven-year-old sister, Annie, and Peanut the mouse ride in a tree house to the Amazon rain forests, where they encounter giant ants, flesh-eating piranhas, hungry crocodiles, and wild jaguars
English stories
Keywords: English fictions